Germplasm Preservation: Storage of Seed, Pollen and Tissue of Selected Malaysian Orchid Species - Kadzimin, Saleh (1987)
In an attempt to develop methods for cheap, long-term preservation of orchid germplasm, seed, pollen and tissue of four local species were subjected to various storage conditions and subsequently determined of their effects on viability. The resultant quality of stored materials varied over the range of conditions and species investigated. Storage of seeds of Arundina graminifolia, Cymbidium finlaysonianum and Spathoglottis plicata at seed moisture content of less than 5 percent and at storage temperature of less than 5°C gave percentage viability that ranged between 60 and 90 percent for a storage duration of more than twelve weeks. Storage in liquid nitrogen (-196°C) gave the highest mean among the temperatures tested, confirming the orthodox nature of the seed.